2006 IEEE Nuclear Science Symposium Conference Record 2006
DOI: 10.1109/nssmic.2006.354269
|View full text |Cite
|
Sign up to set email alerts
|

Light Decay Time/Gain Shift in a LaBr/sub 3/: Ce/LYSO:Ce Phoswich Detector

Abstract: We have found that scintillation light emitted by LaBr 3 is totally absorbed as it passes through an optically joined piece of LYSO on its way to the photocathode of a photomultiplier tube. However, scintillation events in the LaBr 3 reappear as events with a scintillation light decay time similar to the native light decay time of LYSO (40.8 ns) and much greater than the native light decay time of LaBr 3 (17.8 ns). The conversion of LaBr 3 events to scintillations with this new light decay time occurs, for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Green et al [7] looked at phoswich combinations of LaBr 3 :Ce and LYSO:Ce and found that the LaBr 3 :Ce crystal could not be identified due to the interaction between the two crystals. The LaBr 3 :Ce crystal used in their study was Saint Gobain, BrilLanCe 380 with 5% Ce with a fast rise time (< 1 ns) and a ~ 16 ns principal decay time.…”
Section: Introductionmentioning
confidence: 99%
“…Green et al [7] looked at phoswich combinations of LaBr 3 :Ce and LYSO:Ce and found that the LaBr 3 :Ce crystal could not be identified due to the interaction between the two crystals. The LaBr 3 :Ce crystal used in their study was Saint Gobain, BrilLanCe 380 with 5% Ce with a fast rise time (< 1 ns) and a ~ 16 ns principal decay time.…”
Section: Introductionmentioning
confidence: 99%
“…Green et al (7) looked at phoswich combinations between LaBr3 and LYSO and found that the LaBr3 crystal could not be identified due to the interaction between the two crystals. The LaBr3 crystal used in his study was St Gobain, BrilLanCe 380 with 5% Ce with a fast rise time (< 1ns) and a ~ 16 ns principal decay time.…”
mentioning
confidence: 99%